Identification of Organic Migrants from Some Plastic Food Packaging used in Saudi Arabia using Water as Food Simulant - W. KADI, MOHAMMAD; M. ISMAIL, IQBAL; R. SOBAHI, TARIQ (Asian Journal of Chemistry, 2010)
In this study, the authors are interested in organic migrants originating from plastic food-packages used widely in the Saudi market. Instead of using the food itself to conduct experiments food simulant is used, this is to avoid any spectral interferences. Deionized water was used as food simulant which is made to come into contact with the polymer material under desired conditions. GC-MS analysis was used to identify migrants. Many alkyl phthalates and hydrocarbons were found to have been migrated into the food simulant.